Survival in multiple myeloma and SARS-COV-2 infection through the COVID-19 pandemic: Results from the EPICOVIDEHA registry - Musto, Pellegrino; Salmanton-García, Jon; Sgherza, Nicola; Bergantim, Rui; Farina, Francesca; Glenthøj, Andreas; Cengiz Seval, Guldane; Weinbergerová, Barbora; Bonuomo, Valentina; Bilgin, Yavuz M; van Doesum, Jaap; Jaksic, Ozren; et al. (Hematological oncology, 2024)
Patients affected by multiple myeloma (MM) have an increased risk of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection and subsequent coronavirus (20)19 disease (COVID-19)-related death. The changing epidemiological and therapeutic scenarios suggest that there has been an improvement in severity and survival of COVID-19 during the different waves of the pandemic in the general population, but this has not been investigated yet in MM patients. Here we analyzed a large cohort of 1221 patients with MM and confirmed SARS-CoV-2 infection observed between February 2020, and August 2022, in the EPICOVIDEHA registry from 132 centers around the world. Median follow-up was 52 days for the entire cohort and 83 days for survivors. Three-hundred and three patients died (24%) and COVID-19 was the primary reason for death of around 89% of them. Overall survival (OS) was significantly higher in vaccinated patients with both stable and active MM versus unvaccinated, while only a trend favoring vaccinated patients was observed in subjects with responsive MM. Vaccinated patients with at least 2 doses showed a better OS than those with one or no vaccine dose. Overall, according to pandemic waves, mortality rate decreased over time from 34% to 10%. In multivariable analysis, age, renal failure, active disease, hospital, and intensive care unit admission, were independently associated with a higher number of deaths, while a neutrophil count above 0.5 × 109 /L was found to be protective. This data suggests that MM patients remain at risk of SARS-CoV-2 infection even in the vaccination era, but their clinical outcome, in terms of OS, has progressively improved throughout the different viral phases of the pandemic.
Keywords: Multiple Myeloma; mnohočetný myelom; Registries; pandemie; COVID-19; Pandemics; Humans; SARS-CoV-2; lidé; registrace